Strategi Perencanaan Pembiayaan Sekolah dalam Peningkatan Mutu di SMP Negeri - Margareta, Ririn Tius Eka; Ismanto, Bambang (Universitas Kristen Satya Wacana, 2017)
The purpose of this study is to determine the school financing planning strategy in improving the quality of schools. Strategy determination using EFE (Internal Factor Evaluation), IFE (Internal Factor Evaluation), and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. This research is a qualitative research focusing on determining financing planning strategy in SMP Negeri 1 Salatiga. Sources of data come from principals and school treasurers. The technique of collecting data using interviews and documentation. Data analysis included: data collection, data reduction, data display and drawing conclusion/ verification. The result of the research is the appropriate school financing strategy for SMP Negeri 1 is to implement WO strategy or to support defensive strategy that is strategy that minimmize weakness to exploit opportunity. In other words, schools use the number of human resources and limited costs to the maximum by using the funds owned and utilize the role of committees, parents, and alumni. For example, a school can scale priorities together with committee-related competitions to be followed, communicate school needs to the committee in order to improve the quality of education, and submit proposals to alumni to contest, establish school facilities and infrastructure, or salary of honorary teachers/staff.